1982
DOI: 10.1139/x82-109
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of outplanted Douglas-fir seedlings inoculated with mycorrhizal fungi

Abstract: Mycorrhizal and nonmycorrhizal container-grown Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) seedlings were outplanted on dry, burned-over sites in eastern Washington. Prior inoculation of seedlings did not significantly increase survival or height growth, but biomass increment during the first growing season was substantially reduced. New roots of all seedlings became colonized by native mycorrhizal fungi within 5 months after planting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
2
2

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 0 publications
2
13
2
2
Order By: Relevance
“…The EMF colonization rate and fungal species richness of the beech trees in our study were similar to those reported in other studies with young trees (Bledsoe et al, 1982;Wilson and Harley, 1983;Hö gberg, 1989;Dahlberg, 2001;Izzo et al, 2006) but were much lower than in oldgrowth forests, where usually 95% to 99% of the vital root tips are colonized by EMF Näsholm et al, 2013). Therefore, the mean N fluxes, which are similar to those reported by others (for example, Hö gberg, 1989: approximately 4 ng N h À 1 RT À 1 ), may be confounded by NM root tips.…”
supporting
confidence: 91%
“…The EMF colonization rate and fungal species richness of the beech trees in our study were similar to those reported in other studies with young trees (Bledsoe et al, 1982;Wilson and Harley, 1983;Hö gberg, 1989;Dahlberg, 2001;Izzo et al, 2006) but were much lower than in oldgrowth forests, where usually 95% to 99% of the vital root tips are colonized by EMF Näsholm et al, 2013). Therefore, the mean N fluxes, which are similar to those reported by others (for example, Hö gberg, 1989: approximately 4 ng N h À 1 RT À 1 ), may be confounded by NM root tips.…”
supporting
confidence: 91%
“…On the contrary, Danielson (1988) in a study of field competitivity of EMF on jack pine seedlings in western Canada found that Laccaria proxima and Thelephora terrestris had both readily colonized new roots of seedlings after outplanting but were completely superseded by indigenous fungi after one year in the field. In another field study with ectomycorrhizal-inoculated Douglas fir in western North America, Bledsoe et al (1982) obtained similar results: after 5 months, less than 10% of the original seedling feeder roots were mycorrhizal as compared to 20-50% of Laccaria laccata and Hebeloma crustuliniforme mycorrhizae just before outplanting. Furthermore, none of the inoculated fungi were present on the newly formed roots at the base of the root system; these were mainly colonized by indigenous fungi.…”
Section: Discussionmentioning
confidence: 58%
“…Field trials concerning Douglas fir were rarely reported in the literature. Bledsoe et al (1982) observed no positive effects of mycorrhizal inoculation on the growth of Douglas-fir seedlings after outplanting in a dry, burned-over site in eastern Washington, USA, and attributed these unsuccessful results to unsuitable inocula. Enhancement of growth with Douglas-fir seedlings has only been observed in controlledenvironment studies and in nursery situations by Sinclair (1971;1974), Sinclair et al (1982), Bledsoe and Zasoski (1983), Morgan (1985) and Le Tacon and Bouchard (1986).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Danielson and Visser [7] found that Laccaria proxima and Thelephora terrestris were completely superseded by naturally occurring fungi one year after transplantation. Bledsoe et al [3] observed on Douglas fir seedlings that Laccaria laccata and Hebeloma crustuliniforme, previously inoculated in nursery, were unable to colonise new-formed roots in field conditions. Villeneuve et al [29] found that mycorrhizal colonisation by Laccaria species (54%) on Laccaria inoculated Douglas fir seedlings was significantly greater that on controls (13%) two years after transplantation in forest conditions.…”
Section: Introductionmentioning
confidence: 99%